2011
DOI: 10.5539/mas.v5n3p141
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Conditions Necessary for Optimal Cellulase Yield by Cellulolytic Bacterial Organisms as They Relate to Residual Sugars Released in Broth Medium

Abstract: A total of 115 samples made up of 42 (36.5%) rumen fluid, 36 (31.3%) cowdung and 37 (32.2%) soil samples were collected with the aid of sterile swab sticks except for rumen fluid samples which were collected by use of stomach tubes inserted into mouths of cows and by suction, liquor was collected into prewarmed thermo flasks under continuous flushing with carbondioxide. Soil samples were collected into sterile universal containers. All samples were obtained from abattoirs situated at three locations in Benin C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The optimum pH recorded at pH 6.0 in this study supports the findings of Salahuddin et al and Pérez-Avalos et al, who obtained maximum production of β -glucosidase from mesophilic strains of actinomycete and Cellulomonas flavigena , respectively, at pH 6.0 [25, 26]. In the same way, Otajevwo and Aluyi reported maximum degradation of cellulose by Bacillus circulans at pH 6.0 [27]. However, Fawzi [28] reported optimum production of β -glucosidase Fusarium proliferatum NRRL26517 at pH 5.0 while Bansal et al [29] reported pH 7.0 as the optimum which supported maximum production of cellulases by A. niger NS-2.…”
Section: Resultssupporting
confidence: 90%
“…The optimum pH recorded at pH 6.0 in this study supports the findings of Salahuddin et al and Pérez-Avalos et al, who obtained maximum production of β -glucosidase from mesophilic strains of actinomycete and Cellulomonas flavigena , respectively, at pH 6.0 [25, 26]. In the same way, Otajevwo and Aluyi reported maximum degradation of cellulose by Bacillus circulans at pH 6.0 [27]. However, Fawzi [28] reported optimum production of β -glucosidase Fusarium proliferatum NRRL26517 at pH 5.0 while Bansal et al [29] reported pH 7.0 as the optimum which supported maximum production of cellulases by A. niger NS-2.…”
Section: Resultssupporting
confidence: 90%
“…The longer incubations make the bacterium capable of taking up maximum nutrients required for necessary cellular, metabolic or physiological changes prior to each binary fission. The enhancement in cellulase production by B. tequilensis G9 from basal level (OVAT approach) of 21.98 IU/ml extract to optimized 32.65 IU/ml extract in PB design followed by 44.02 IU/ml extract under RSM analysis was much higher than that of the optimal cellulase activities of Bacillus circulans (4.80 IU/ml), Bacillus subtilis (4.64 IU/ml), Clostridium thermocellum (5.32 IU/ml), at pH 6 after incubation at 40 °C [24]. Our results of cellulase activity were also higher than the activities observed by many authors [25][26][27] using PB design and RSM for optimization of cellulase production with Cellulomonas flavigena after 48 h. The probable reason for this higher activity could be variation in culture conditions and media used by the researchers previously.…”
Section: Discussionmentioning
confidence: 92%
“…Hatami et al ( 2008 ) isolated aerobic cellulolytic bacteria from forest and farming soils and determined their ability to decompose cellulose. In another study, Otajevwo and Aluyi ( 2010 ) isolated Pseudomonas sp. YJ5 from soil samples, and cellulase activity was determined after 48 h of incubation.…”
Section: Introductionmentioning
confidence: 98%